PENGGUNAAN METODE SQ3R UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR: TINJAUAN LITERATUR - Ispar, Maisarahtul; Khoirunnisa; Habibi, M. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading comprehension skills among elementary school students are still relatively low. Many students have difficulty understanding texts, identifying main ideas, and answering questions based on reading materials. This condition is influenced by low reading interest and less effective teaching methods. Therefore, an appropriate learning method is needed to help students read actively and systematically, one of which is the Survey, Question, Read, Recite, and Review (SQ3R) method. This study aims to analyze the use of the SQ3R method in improving elementary school students’ reading comprehension skills through a literature review. The research method used was a Systematic Literature Review (SLR) with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) model. Data sources were obtained from scientific articles published between 2016 and 2026 through Google Scholar and Semantic Scholar databases using the Publish or Perish application. A total of 40 relevant articles were identified and selected based on inclusion and exclusion criteria. The findings indicate that the SQ3R method effectively improves reading comprehension skills, reading interest, student participation, and learning outcomes in elementary schools. Therefore, the SQ3R method can be used as an effective alternative learning strategy in Indonesian language learning.